Politik Gender dan Kontestasi Maskulinitas di Media Sosial: Analisis Representasi Emil Mario dalam Ruang Digital - Chanila Misya Subkhan; Ezra Kalyla; Ika Arinia Indriyany (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the construction of masculinity and femininity meanings through gender expression represented by the Indonesian digital creator Emil Mario on social media platforms. Using an empirical qualitative approach with a case study design, the research analyzes digital content from TikTok and Instagram, including visual performances, narrative captions, and audience interactions. Data were collected through digital ethnography, documentation of online content, and analysis of public discourse surrounding the creator’s gender expression. The findings reveal that gender identity in digital spaces is constructed through repeated performative practices manifested in visual aesthetics, body gestures, fashion choices, and narrative self-representation. These performative elements contribute to the formation of a distinctive digital persona that challenges conventional norms of hegemonic masculinity in Indonesian society. Audience responses further demonstrate the presence of discursive contestation between traditional patriarchal expectations and more flexible interpretations of gender identity. From a socio-legal perspective, the phenomenon reflects broader debates concerning freedom of expression, non-discrimination, and gender politics in digital public spaces. The study concludes that social media functions as a significant arena where gender identities are negotiated, contested, and reconstructed within contemporary digital culture.